A tuneable active inductor employing DXCCTA: Grounded and floating operation. (August 2019) - Kumar, Navnit; Vista, John; Ranjan, Ashish
Abstract: An active inductor employing both grounded as well as floating mode using Dual-X Current conveyor Transconductance Amplifier (DXCCTA) is presented in this article. The novelty of the proposed inductor topology is to exhibit simultaneously both positive and negative inductor characteristics without any change in the topology. In addition, active realization of positive and negative fractional order inductor are also presented. The performance characteristics of the proposed inductor models are verified using CMOS as well as Current Feedback Operational Amplifier (CFOA/IC AD844) based DXCCTA block. The compatibility of the proposed inductors is suitable for various application viz. active filter design using positive inductor and inductance cancellation using negative inductor. The theoretical explanations of the proposed designs are well verified through PSPICE simulations and experimental platform.